1993
DOI: 10.7209/tanso.1993.177
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Carbon Fiber with Tetrafluoromethane Plasma

Abstract: Surface modification of carbon fiber by cold plasma of tetrafluoromethane was investigated.PAN-based and pitch-based carbon fibers were used.Plasma treatment was carried out by high-frequency discharge in tetrafluoromethane.The surface of carbon fiber was modified to be hydrophobic by treatment. The carbon fiber underwent heat-treatment or immersion in water, after which stability of the fluorine introduced was examined by measuring the contact angle with water, fluorine content, and estimating F/C in ESCA spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ohte et al n reported that three types of fluorine groups are introduced by plasma treatment: 1) covalent bond type, insoluble in water and stable to heat, 2) layer interstitial type, insoluble in water and unstable to heat, and 3) adsorption type, soluble in water and unstable to heat. To provide a more hydrophobic surface, a carbon fiber was used as the tetrafluoromethane plasma treatment surface 11 . Thus, it is considered that the interaction between the adsorbates containing fluorine atoms in the molecule and the surface of the activated carbon is extremely large.…”
Section: Resultsmentioning
confidence: 99%
“…Ohte et al n reported that three types of fluorine groups are introduced by plasma treatment: 1) covalent bond type, insoluble in water and stable to heat, 2) layer interstitial type, insoluble in water and unstable to heat, and 3) adsorption type, soluble in water and unstable to heat. To provide a more hydrophobic surface, a carbon fiber was used as the tetrafluoromethane plasma treatment surface 11 . Thus, it is considered that the interaction between the adsorbates containing fluorine atoms in the molecule and the surface of the activated carbon is extremely large.…”
Section: Resultsmentioning
confidence: 99%
“…They are caused due to fluorine atoms or 0 atoms introduced by plasma treatment and generated radical. [6]- [8] . The mechanism of elapsed change also has been analyzed [6]- [8].…”
mentioning
confidence: 99%
“…[6]- [8] . The mechanism of elapsed change also has been analyzed [6]- [8]. However, it is the merit of the plasma surface modification that the material can be modify at low temperature.…”
mentioning
confidence: 99%